2010
DOI: 10.4995/wrs.2008.640
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects on semen quality in Black Baladi and White New Zealand rabbit bucks.

Abstract: A total of 32 sexually mature rabbit bucks (at 6 th month of age) were used in this experiment to study the effects of breed (Black Baladi -BB-vs. White New Zealand -WNZ-) and season (summer vs. winter) on libido and seminal parameters. The experimental design was completely random with four groups arranged factorially (two breeds and two seasons) with eight rabbits in each group and three months per season. The results obtained from this study indicated that, libido (14.5 vs. 21.9 sec) and physical semen char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The results of the present work evidently demonstrated that the success of cryopreservation mainly depends on the effect of seasonality on fresh semen from the beginning of semen processing. The results for fresh and cryopreserved semen (Table 1, 2) revealed that there was no significant difference between semen quality parameters during autumn, winter and spring seasons, but the highest values of the total motility, live sperm, functional membrane integrity and acrosome integrity were yielded in winter, which is in agreement with previous studies by Marai et al (2002) and Safaa et al (2008). This may be attributed to the fact that rabbits can tolerate up to about 27°C degrees without heat stress or adverse effect on semen characters.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present work evidently demonstrated that the success of cryopreservation mainly depends on the effect of seasonality on fresh semen from the beginning of semen processing. The results for fresh and cryopreserved semen (Table 1, 2) revealed that there was no significant difference between semen quality parameters during autumn, winter and spring seasons, but the highest values of the total motility, live sperm, functional membrane integrity and acrosome integrity were yielded in winter, which is in agreement with previous studies by Marai et al (2002) and Safaa et al (2008). This may be attributed to the fact that rabbits can tolerate up to about 27°C degrees without heat stress or adverse effect on semen characters.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the EZ0 rabbit bucks presented a lower sexual drive than the EZ-supplemented rabbit bucks, coincident with a linear increase in blood testosterone levels with ascending levels of the diet EZ additive. The reaction time of rabbit bucks was much longer than the 4.2 s observed by Ogbuewu et al (2009) with New Zealand white×Chinchilla rabbit bucks and 14-21 s reported by Safaa et al (2008) in Black Baladi and White New Zealand rabbit bucks. This may be due to the testosterone and estradiol, which act synergistically to stimulate male sexual behaviour (Cross and Roselli, 1999).…”
Section: Discussionmentioning
confidence: 49%
“…El-Sawy et al, (2017); Lavara et al, (2013) and Safaa et al, (2008) reported that the libido, mating activity and the physical semen quality of NZW rabbit bucks during the winter season were highly significant (P≤0.01) better than those observed in the summer season. Semen volume increased and motility indexes decreased during summer (Roca et al, 2005).…”
Section: -5-fertility Of Bucks and Semen Qualitymentioning
confidence: 99%